(untitled) (Dhaka University Journal of Biological Sciences, 2015)
Middle mountain areas of Nepal Himalaya is seriously suffering from ecological degradation and an estimation of over 240 million cubic meter of top soil is being eroded annually to the Bay of Bengal. Thirteen per cent of Nepal’s watershed area have deteriorated seriously and 10,000 sq km are devoid of sufficient vegetation. Top soil loss from the mountain results in the riverbeds’ raise at a annual rate of 15 ‐ 30 cm and its effect on soil fertility declines. Considering this, an attempt was made to estimate the soil loss using GI Science technology and its correlative interpretation with land system units and land use and cover types from Maheshkhola watershed. Among several empirical and physically‐based erosion models, Revised USLE (RUSLE) using RKLSCP was used to estimate the soil loss in the present analysis. A total of 231,155 ton soil was estimated annually being lost from Maheshkhola watershed. Erosion rates were found highly associated with the slope of land system units. Thirty three per cent of the total soil loss were mainly contributed only by each land system units, 11 and 12. Depositional dissected alluvial fan was found highest of 3.62 t/ha/yr soil loss among the averages. Agriculture as a dominant human activity, spatially concentrated in 61.53% of the watershed area, was contributing significantly as of 90% of the total soil loss in the study area. Similarly soil cliff/landslide and river sand areas contributed 10.11 t/ha/yr and 9.38 t/ha/yr on an average, respectively. The land units, steeply mountainous terrain having soil loss more than 35 t/ha/yr must be given higher priorities for soil conservation. Dhaka Univ. J. Biol. Sci. 24(2): 177-189, 2015 (July)